Involvement of BDNF in Age-Dependent Alterations in the Hippocampus - Von Bohlen Und Halbach, Oliver (Frontiers in Aging Neuroscience, 2010)
It is known since a long time that the hippocampus is sensitive to aging. Thus, there is a reduction in the hippocampal volume during aging. This age-related volume reduction is paralleled by behavioral and functional deficits in hippocampus-dependent learning and memory tasks. This age-related volume reduction of the hippocampus is not a consequence of an age-related loss of hippocampal neurons. The morphological changes associated with aging include reductions in the branching pattern of dendrites, as well as reductions in spine-densities, reductions in the densities of fibers projecting into the hippocampus as well as declines in the rate of neurogenesis. It is very unlikely that a single factor or a single class of molecules is responsible for all these age-related morphological changes in the hippocampus. Nevertheless, it would be of advantage to identify possible neuromodulators or neuropeptides that may contribute to these age-related changes. In this context, growth factors may play an important role in the maintenance of the postnatal hippocampal architecture. In this review it is hypothesized that brain-derived neurotrophic factor (BDNF) is a factor critically involved in the regulation of age-related processes in the hippocampus. Moreover, evidences suggest that disturbances in the BDNF-system also affect hippocampal dysfunctions, as e.g. seen in major depression or in Alzheimer disease.